High-efficient method of determination of a dynamic characteristic of the analog-to-digital converter - Kichak, Vasyl; Bortnyk, Sergii; Punchenko, Natalya (Видавництво Львівської політехніки, 2010)
The effective method of determination of dynamic characteristics of the analog-to-digital converter which at the expense of use of a pseudo-random test signal gives the possibility to increment efficiency and reliability of a method is presented in work.
Keywords: Analog-to-digital converter; dynamic characteristic; inaccuracy